ثقافة الاستغراب في الفكر العربي المعاصر (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
يعد التعرف على علم الاستغراب الذي ظهرت ملامحه في الفكر العربي المعاصر عند المفكر حسن حنفي، والمساهمة في تطويره بتحديد معالمه أولاً وبنقده ثانياً.هو اليوم أمراً مَطلوباً بل مُلِحاً لتفادي الوقوع في سياج هوية حضارية عربية مُتشنجة رافضة للغير بحكم مسبق وبفكر نصي قطعي لا يقل صعوبة عن قطعية ومحدودية العقل الأصولي السلفي المُحرم للاجتهاد والتعقل والمواكبة. ويتناول البحث ضرورات تكوين علم الاستغراب على نحو تكون فيه الأنا العربية نزيهة من ما تلوث أنا الاستشراق الغربي الاستعماري الثقافي غير المباشر بعيداً عن مواقف رد الفعل المتمركزة على محور غطرسة الذات نحو فكر علمي عربي نهضوي همه الأوحد هو مواكبة العالم ودخول التاريخ مع صون الأنا دون ضرر ولا ضرار. وذلك بتحليل ظاهرة تفوق الغرب والتحري عن مفاتيح القدرة و وأسبابها والتنقيب عن أسباب انصهارنا في بوتقة الحضارة الغربية، للحد من الانبهار المُبالغ فيه بها وذلك بهدف التخلص – أو إضعاف على أقل تقدير - من ثنائية شمال وجنوب أو عرب وغرب للوصول إلى حالة المشاركة العالمية في صنع مقومات الحضارة والكف عن حالة التبعية والأخذ دون مقابل.  ودون ذلك لن تصحح صورة العربي والمسلم أمام نفسه أولاً وأمام العالم ثانياً. إذاً هذا البحث هو محاولة للتركيز على الدور الريادي للعربي والمسلم في إمكانيته على تكوين آلية فكرية ليست براغماتية بل علمية  تضمن مواكبة عجلة التاريخ دون صدام ودون تبعية. مما يحتم علينا التطرق لنقد مسألة الاستشراق كونها الفكر الذي يقف على الضفة المقابلة للفكر الاستغرابي. وخاصة أن الغرب اليوم وبالتحديد أمريكا لا تتوانى على الحصول على أي مخطوط عربي ينتقدها وينتقد عنصريتها لتضعه في عين الاعتبار بما يخدم مركزيتها  أو لمحاولة  شراء الأدمغة العربية التي تفكر لصالح الهوية العربية والإسلامية  لجعلها تعمل لحساب منهجيتها فلابد أن تكون إمبرياليتها ليست محض صدفة بل مبنية على كثير من السعي الدؤوب والمواكبة بلا كلل ولا ملل. to know  the science of  westernism whose features  appeared in  contemporary Arab thought by the  thinker Hassen Hanafi, and contribution  in its  development via identifying its  features first; "and to criticize it  Second." is today considered to be a must, but rather urgent "to avoid having fallen  in the limit of an Arab civilized identity which is  convulsive and rejecting the other through a predetermined  judgment and a textual thought which is undebatable and  not  less  difficult  than the undebntability and darkness of the fundament alist  salafi mind that  forbids diligence, rationality and development.                                                                           The research deals with the needs to form the science of westernism as per the arab ego to be pure and free from western colonial cultural orientalism indirectly, being far from reaction as centeralized on the axis of self-arrogance towards uprising arab scientific thought  whose concern is to keep abreast of the world and go into history with keeping up the ego safe and secure, through analyzing the phenomenon of western superiority and detecting the keys of power and its reasons to find why we are fused in the western civilization. This is to stop being fascinated excessively by that, to get rid of that or to lessen the duality of south and north or arabs and the western to get to a state of international participation in making the pillars of civilization, and to stop being annexed to the west and taking with no return. Not doing that, the picture of the arab and the muslim will not be corrected for themselves first and for the world second. Thus, this research is an attempt to focus on the leading role of arabs and muslims to have a thought mechanism, not pragmatic but scientific to keep abreast of history force with no clash or being annexed, so it should be noted that orientalism is a thought that stands on the opposite bank of the westernized  thought . today, the west is especially fully ready to get any Arabic text to criticize it, including  America, and to criticize its racism in order to be considered as serving their centrality in an attempt to make arab drain purchased especially those who think of the arab Islamic identity to have them work for their mythodology because this colonialism is not pure coincidence, but it is based on hardworking pursuit in avery tireless way.